THE ROLE OF PASSIVE VOICE IN ACADEMIC WRITING (Ustozlar uchun, 2026)
Passive voice has long been recognized as one of the most typical grammatical features of academic writing in English. Although modern academic style increasingly allows limited use of active constructions, passive structures still play a central role in scientific writing. This article examines the language, functions, and style of passive voice in academic writing. The study looks into its grammatical structure, communicative purposes, variations across disciplines, advantages and disadvantages, and its changing role in current research writing. The analysis shows that passive constructions contribute to objectivity, depersonalization, and a formal tone while also influencing the informational structure of academic texts.